SELECTION ANALYSIS OF ROAD MAINTENANCE METHODS BETWEEN THE USE OF SLURRY SEALS AND SPOT LEVELLING FROM SERVICE LIFE AND CONSTRUCTION COSTS ASPECTS - Utomo, Tri Cahyo; Prastyanto, Catur Arif (Journal of Civil Engineering, 2023)
On national roads (arterial roads) whose LHR conditions should be the same or tend to be higher than provincial roads (collector roads) still often use slurry seals for handling to protect the asphalt layer from disintegration, cracking and reduced skid factor on the road. In fact, in its implementation on provincial roads, the lifespan of spot leveling works tends to have a much longer service life than slurry seals which tend to be damaged during the same fiscal year. This is certainly a contradictory conclusion between the two methods applied, namely on provincial roads with LHR tend to be lower than national roads using spot leveling treatment which has a longer lifespan, while on national roads it is the other way around. With the above problems, it is necessary to do further research on the factors that underlie the selection of the method, the service life of the results of the handling is compared to the construction costs incurred. The research method was carried out using LHR data to determine the condition of traffic loads on each segment of the segment, survey road conditions to determine the percentage of damage and the remaining service life of slurry seals and spot leveling, and compared with construction costs. The CESA value or traffic load characteristics affect the service life of the slurry seal, with a service life gap of 2.08 years and handling cost of Rp. 12,949.29 per square meter per year. Drainage conditions also influence the service life of the slurry seal, with a service life gap of 1.32 years and handling cost of Rp. 8,097 per square meter per year. Sidewalk conditions impact the service life of the slurry seal as well, with a service life gap of 0.52 years and handling cost of Rp. 4,688.39 per square meter per year. Based on the data on the service life gaps and handling costs, the most influential factor on the service life and duration of the slurry seal is the CESA condition on the road segment where the slurry seal is applied.